It Happened to a Friend of Mine: The Influence of Perspective-taking on the Acknowledgment of Sexual Assault Following Ambiguous Sexual Encounters - Lamarche, Veronica M. (Journal of interpersonal violence, 2022)
Failure to acknowledge that one has been the victim of sexual violence is an important, yet understudied, barrier that prevents women from seeking appropriate support following sexual violence. Drawing from a literature of demonstrating the benefits of self-distancing when evaluating emotionally charged personal information, the effects of self-distancing on acknowledgment of sexual assault were tested. Four experimental studies (Ntotal = 1,609) manipulated perspective-taking, either by asking women to imagine a series of hypothetical sexual encounters as experiences that happened to themselves or to their friends, or by asking women to describe a sexual experience from a first- or third-person perspective. Findings from the studies suggest that taking another person?s perspective can help women to label ambiguous sexual experiences as more inappropriate and coercive. Notably, this did not seem to stem from women downplaying or dismissing experiences when they imagined themselves, as they reported anticipating more negative and less positive emotions in the scenarios where they imagined themselves compared to a friend. Nonetheless, in spite of the stronger anticipated negative emotional response when imagining themselves, women were less open to information about resources associated with sexual assault and support when they imagined themselves compared to a friend. This pattern of findings replicated for own, past sexual experiences but only to the extent that women spontaneously engaged in distanced perspective-taking themselves. This research suggests in addition to using contextual information to disambiguate and determine whether a sexual experience was inappropriate, taking a distanced perspective might provide a route through which women can come to terms with the experience and open up to the use of community-based services and sexual assault resources.